PTEN expression and mutations in TSC1, TSC2 and MTOR are associated with response to rapalogs in patients with renal cell carcinoma - Roldan‐Romero, Juan M.; Beuselinck, Benoit; Santos, María; Rodriguez‐Moreno, Juan F.; Lanillos, Javier; Calsina, Bruna; Gutierrez, Ana; Tang, Karin; Lainez, Nuria; Puente, Javier; Castellano, Daniel; Esteban, Emilio; et al. (International journal of cancer, 2020)
The mammalian target of rapamycin (mTOR) pathway inhibitors are key drugs for the treatment of many tumor types, however, there are no predictive biomarkers in clinical use. Here, we performed a molecular and immunohistochemical characterization of key mTOR pathway components in a series of 105 renal cell carcinoma patients treated with rapalogs, aimed at identifying markers of treatment response. Mutational analysis in MTOR, TSC1 and TSC2 was performed through targeted next‐generation sequencing (NGS), and immunohistochemistry (IHC) was performed for PTEN, pAKT, pS6K1, pS6 and p21. Among patients with NGS data, 11 of 87 (13%) had mTOR pathway mutations (8 in MTOR, 1 in TSC1 and 2 in TSC2). When comparing the molecular data to the response of the patients, we found that partial response was more frequent in cases with mTOR pathway mutations than in those without mutations (odds ratio [OR] = 0.08, 95% confidence interval [CI] = 0.008–0.79, p = 0.030 univariate; p = 0.038 multivariable). Regarding IHC, negative PTEN staining was detected in 58% of the tumors, and it was more frequent in rapalog responder patients (OR = 0.24, 95% CI = 0.065–0.86, p = 0.029 univariate; p = 0.029 multivariable). Mutations and PTEN IHC were not mutually exclusive events and its combination improved response prediction (OR = 0.16, 95% CI = 0.04–0.62, p = 0.008 univariate; p = 0.013 multivariable). The staining of other proteins did not show and association with response and no association with PFS was observed in unselected patients. In conclusion, our findings suggest that mTOR pathway mutations, negative PTEN IHC and their combination are potential markers of rapalog response. What's new? Inhibitors of the mammalian Target of Rapamycin (mTOR) are key drugs for the treatment of renal cell carcinoma. However, only a subset of patients benefits clinically, and it is unclear why. Here the authors identified mutations in mTOR pathway, as well as loss of expression of the tumor suppressor PTEN, as markers of favorable outcome, underscoring the potential of these markers– either alone or in combination – to serve as clinical tools for patient stratification.